Internet Geography and Real Estate Market - Dan Komosny (IEEE Access, 2017)
This paper introduces a new spatial data resource for Internet geography. The idea is based on merging two up-to-now unrelated fields-the real estate market and Internet networking. The huge real estate market is present almost everywhere, and therefore, it is a valuable resource for trusted spatial data when connected to cyber space. We describe a method that gains spatial data from the real estate market and links this data to cyber space. We support the method by a real implementation. Based on the collected data, we identified the geographical scope of a set of Web servers. The new data in cyber geography may help in the Internet Web-related market competition.